Let h(x) = (g o f)(x) = sqrt{x+3}
2 answers:
I am assuming you meant to write the following options
A. f(x)=x+3; g(x)=√x
B. f(x)=x; g(x)=x+3
C. f(x)=√x; g(x)=x+3
D. f(x)=3x; g(x)=√x
You need to find a fucntion f(x) that once evaluated in g(x) gives us as a result h(x)
h(x) = g(f(x))
Looking at the options, the answer is A.
g(f(x)) = sqrt(f(x)) = sqrt (x + 3) = h(x)
Answer:
The answer is f(x)=x+3; g(x)=sqrt x
Apex
Step-by-step explanation:
You might be interested in
Answer:the answer is B
Step-by-step explanation:Bisect each of the angles with vertices at their houses
Step-by-step explanation:
the solution is in the picture
Answer:
Answer B
Step-by-step explanation:
Whatever happened to just normal 70 times 6,000? The product is 420,000. If that was your question.
Answer:
a triangle as 3 sides
Step-by-step explanation: